2019
DOI: 10.1002/jcph.1392
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Vancomycin Dosing Guideline in the Neonatal Intensive Care Unit for Achieving Goal Therapeutic Trough Concentrations

Abstract: Concern for bacterial resistance and treatment failure with vancomycin trough concentrations < 10 μg/mL have led guidelines to increase goal concentrations. There is a paucity of data evaluating vancomycin dosage necessary to achieve goals in the neonatal intensive care unit (NICU). We aimed to evaluate the implementation of a new vancomycin dosing guideline in improving trough target attainment. This retrospective study evaluated neonates in the NICU treated with vancomycin between January 2009 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Nine studies (45% of relevant studies; 1940 children) found an association between vancomycin levels and v-AKI 17 19 21 25 29 31 32 35 38. Eleven studies (55% of relevant studies; 3234 children) showed no association 16 18 20 26 28 30 32 34 36 37 39. A final vancomycin trough concentration above the local threshold of ≥15 mg/L was reported to be an independent risk factor for v-AKI in children in several studies19 25 29 31 38 and this was confirmed by Zhang et al in multivariate analysis 17.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…Nine studies (45% of relevant studies; 1940 children) found an association between vancomycin levels and v-AKI 17 19 21 25 29 31 32 35 38. Eleven studies (55% of relevant studies; 3234 children) showed no association 16 18 20 26 28 30 32 34 36 37 39. A final vancomycin trough concentration above the local threshold of ≥15 mg/L was reported to be an independent risk factor for v-AKI in children in several studies19 25 29 31 38 and this was confirmed by Zhang et al in multivariate analysis 17.…”
Section: Resultsmentioning
confidence: 77%
“…This study includes a total of 12 730 paediatric patients with a median age of 2.5 years (range 0–23), and 57% were male patients. There was missing age17 18 and gender data19 20 in two studies each. The median dose of vancomycin was 43.3 mg/kg/day (range 14.9–60.0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current landscape of multiple dose recommendations pose difficulties on the clinicians to determine dose that can achieve target AUC/MIC goals. This has led institutions to adopt their own measures of developing internal dosing recommendations based on clinical variables collected from their own specific patient population and through stimulation of real-world data (26,27). Recent studies have also demonstrated the value of using population pharmacokinetic data to personalize empirical vancomycin dosing.…”
Section: Discussionmentioning
confidence: 99%